2023
DOI: 10.3390/pharmaceutics15010221
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Solid Lipid Nanoparticles for the Clearance of Aβ in Alzheimer’s Disease

Abstract: Aggregation of Amyloid-β (Aβ) leads to the formation and deposition of neurofibrillary tangles and plaques which is the main pathological hallmark of Alzheimer’s disease (AD). The bioavailability of the drugs and their capability to cross the BBB plays a crucial role in the therapeutics of AD. The present study evaluates the Memantine Hydrochloride (MeHCl) and Tramiprosate (TMPS) loaded solid lipid nanoparticles (SLNs) for the clearance of Aβ on SHSY5Y cells in rat hippocampus. Molecular docking and in vitro A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Similarly, NLCs are modified SLNs in which the lipid phase consists of liquid lipids (oils) and solids at room temperature . The small size and lipid nature of SLNs and NLCs facilitate crossing the BBB, especially in the leaky tumor vasculature. , Regarding drug delivery to the CNS, both SLNs and NLCs have been confirmed to improve the treatment of several neurological diseases, such as Parkinson’s disease, Alzheimer’s disease, migraine, epilepsy, and brain cancer . Many studies demonstrated the superiority of NLCs and SLNs over other nanoparticles (e.g., PLGA NPs) to promote targeted delivery of drugs to the brain due to their lipid properties. …”
Section: Permeation Mechanisms Of Nanoparticles Capable Of Crossing T...mentioning
confidence: 99%
“…Similarly, NLCs are modified SLNs in which the lipid phase consists of liquid lipids (oils) and solids at room temperature . The small size and lipid nature of SLNs and NLCs facilitate crossing the BBB, especially in the leaky tumor vasculature. , Regarding drug delivery to the CNS, both SLNs and NLCs have been confirmed to improve the treatment of several neurological diseases, such as Parkinson’s disease, Alzheimer’s disease, migraine, epilepsy, and brain cancer . Many studies demonstrated the superiority of NLCs and SLNs over other nanoparticles (e.g., PLGA NPs) to promote targeted delivery of drugs to the brain due to their lipid properties. …”
Section: Permeation Mechanisms Of Nanoparticles Capable Of Crossing T...mentioning
confidence: 99%
“…However, the specific neuroprotective mechanisms remain unclear. In this approach, Shivananjegowda et al [ 13 ] found that SLNps formulated using memantine hydrochloride (MeHCl) and tramiprosate (TMPS) confirmed the metabolic degradation of A β on SH-SY5Y cells.…”
Section: Introductionmentioning
confidence: 99%
“…A tricyclic antidepressant (TCI) is also used for neuroleptic pain . AMX is also used to reduce antibiotic resistance and inhibit mycobacterial infections . AMX is an N-desmethyl derivative of loxapine with noradrenaline reuptake inhibition, 5-HT receptor antagonism, and dopamine D2 receptor antagonism .…”
Section: Introductionmentioning
confidence: 99%
“…SLNs and other nanoparticle formulations can increase drug bioavailability. In recent studies, memantine hydrochloride (MeHCl) and tramiprosate (TMPS)-loaded solid lipid nanoparticles were prepared to treat Alzheimer’s disease . SLN is a suitable delivery system for poorly aqueous-soluble drugs due to its biocompatible lipids and ability to entrap lipophilic molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation